Per una storia dei processi formativi: intersezioni, costrutti euristici e problemi aperti - Ferrari, Monica (Studi sulla Formazione/Open Journal of Education, 2009)
It’s important, today, reflect about formative processes and on their historical develop. This history is a string of knowledges that gains importance through the dialogue between other disciplines. It’s necessary to start from childhood history to build a heuristic immagine of that argument and read again classical authors.